2008
DOI: 10.1089/hum.2008.131
|View full text |Cite
|
Sign up to set email alerts
|

Misinterpreting the Therapeutic Effects of Small Interfering RNA Caused by Immune Stimulation

Abstract: Activation of innate immunity has direct effects in modulating viral replication, tumor growth, angiogenesis, and inflammatory and other immunological processes. It is now established that unmodified siRNA can activate this innate immune response and therefore there is real potential for siRNA to elicit nonspecific therapeutic effects in a wide range of disease models. Here we demonstrate that in a murine model of influenza infection, the antiviral activity of siRNA is due primarily to immune stimulation elici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
0
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(143 citation statements)
references
References 31 publications
2
136
0
5
Order By: Relevance
“…Extending the CED delivery beyond the current dosing period of 14 d may offer additional survival benefit when siRNA dosing limits per unit vehicle are in place with the current nano packaging technologies. Although there could be concerns about the potential for nonmodified siRNA duplexes to induce innate immune response for antitumor effects (75,76), our use of nu/nu mouse models with human BTIC xenografts and the universal nontargeting negative siRNA controls mitigated this common misinterpretation of antitumor results. For clinical translation, this potential impact will be assessed in immune-competent mouse models, which could reveal the impact of these LPNPs on the immune response of GBM.…”
Section: Discussionmentioning
confidence: 99%
“…Extending the CED delivery beyond the current dosing period of 14 d may offer additional survival benefit when siRNA dosing limits per unit vehicle are in place with the current nano packaging technologies. Although there could be concerns about the potential for nonmodified siRNA duplexes to induce innate immune response for antitumor effects (75,76), our use of nu/nu mouse models with human BTIC xenografts and the universal nontargeting negative siRNA controls mitigated this common misinterpretation of antitumor results. For clinical translation, this potential impact will be assessed in immune-competent mouse models, which could reveal the impact of these LPNPs on the immune response of GBM.…”
Section: Discussionmentioning
confidence: 99%
“…The siRNA component of CALAA-01 is not chemically modified. Much preclinical work has demonstrated that nonchemically modified siRNAs can be immunostimulatory under certain conditions (16). Specifically, systemic administration of siRNA with lipid carriers can cause significant immunostimulation.…”
Section: Mild Dose-dependent Elevations In Serum Cytokines Followingmentioning
confidence: 99%
“…RNAi can cause expression suppression in genes homologous to the desired gene, and produce effects which were not the result of the silencing of the target gene. In early tests of siRNA therapies in small animals, the effects produced by the therapies may not have been from the target knock-down at all, but from the off-target effects [82,113]. Additionally, RNA sensors in the innate immune system can prohibit effective RNAi by triggering the release of interferons.…”
Section: Obstacles In Therapeutic Rnaimentioning
confidence: 99%
“…However, entering the cell from the bloodstream is still a hurdle. Because of their negative charge and high molecular weight, siRNAs cannot cross the plasma membrane [82,113]. Cells can uptake siRNAs through endocytosis, but then the siRNA is trapped within an endosome, and cannot produce gene knock-downs.…”
Section: Obstacles In Therapeutic Rnaimentioning
confidence: 99%